Analysis of rhizosphere fungal diversity in lavender at different planting years based on high-throughput sequencing technology. - Xia Deng; Renzeng Shi; Rehab O Elnour; Zixuan Guo; Junzhu Wang; Wenwen Liu; Guihua Li; Ziwei Jiao (PLoS ONE)
Continuous cropping is a common cultivation practice in lavender cultivation, and the structure of the soil microbial community is one of the main reasons affecting the continuous cropping disorder in lavender; however, the relationship between the number of years of cultivation and inter-root microbial composition has not yet been investigated; using Illumina high-throughput sequencing we detected fungal community structure of rhizosphere soil under 1 (L1), 3 (L3), 5 (L5) and 0 (L0) years' of lavender cultivation in Yili, Xinjiang China. The results showed that with the extension of planting years, the physical-chemical characteristics of the soil shifted, and the diversity of the fungal communities shrank, the abundance and richness of species decreased and then increased, and the phylogenetic diversity increased, The structure of the soil fungal communities varied greatly. At phylum level, dominant fungal phyla were Ascomycetes, Basidiomycetes, etc. At genus level, dominant genera were Gibberella, Mortierella, etc, whose absolute abundance all increased with increasing planting years (P < 0.05); redundancy analysis showed that thesoil physicochemical characteristics significantly correlated with dominant bacterial genera. The FUN Guild prediction showed that six groups of plant pathogens and plant saprotrophs changed significantly (P < 0.05), the amount of harmful bacteria in the soil increased while the amount of arbuscular mycorrhizal fungui (AMF) decreased, leading to a continuous cropping obstacle of lavender. The findings of this study provida theoretical foundation for the management of continuous cropping and the prevention fungus-related diseases in lavender.